Regaining Control of Your Email - Gian S Pagnucci; Ethan W Krase (Academic Chairpersons Conference Proceedings, 2016)
This session will introduce department chairpersons and administrators to a variety of email management techniques for helping perform one’s job more effectively. The presentation will cover email management techniques and practical strategies. Attendees will leave with new ideas for how to manage email more effectively and thereby reduce stress levels.
Keywords: email; time management; task management; productivity; stress reduction